FUNGSI REKRUTMEN POLITIK PADA CALON LEGISLATIF PARTAI KEBANGKITAN BANGSA (PKB) 2009 - Ainur Rofieq (Governance, 2011)
This paper aims to determine the recruitment process of political parties that occured amidst the political parties that are in conflict, as happened in the PKB. The conflict clearly resulted in the party cohesiveness is reduced so the question arises how the recruitment process and how the representation of woman in the recruitment process. The process happens by looking at the number of legislators elected on Election 2004 and Election 2009.